1981
DOI: 10.1002/pol.1981.170190905
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic relationships and mechanism of ozone reaction with polystyrene in CCl4 solution

Abstract: In this work a study is made of the degradation on ozonation of unfractionated polystyrene (PS) in CCl4 solution. It was found that the ozone attack of PS molecules is accompanied by hydrogen abstraction from tertiary CH bonds and by the formation of ozonides due to the reaction of ozone with the aromatic rings. A scheme of PS degradation in solution is suggested; several kinetic parameters are evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In fact, formation of peroxides has been reported during the oxidation of other plastics. 31,32 Unfortunately, the photolysis of ozone induces a slightly blue colour and a high fluorescence background in the oxidized plastics. Consequently, this method is not suitable for the surface modification of plastics devices that are based on fluorescence detection.…”
Section: Surface Chemistry and Immobilization Of Dna On Poly(cyclic Omentioning
confidence: 99%
“…In fact, formation of peroxides has been reported during the oxidation of other plastics. 31,32 Unfortunately, the photolysis of ozone induces a slightly blue colour and a high fluorescence background in the oxidized plastics. Consequently, this method is not suitable for the surface modification of plastics devices that are based on fluorescence detection.…”
Section: Surface Chemistry and Immobilization Of Dna On Poly(cyclic Omentioning
confidence: 99%
“…The MALDI mass spectrum for this polymer closely resembled the ozonolysis/MALDI mass spectrum for polybutadiene in Figure . Since the reaction rate constant for ozonolysis of polybutadiene is approximately 6 orders of magnitude greater than for ozonolysis of polystyrene, , the absence of signals in the mass spectra due to styrene oligomers is not surprising. After 2 h of ozonolysis, the mass signals due to butadiene oligomers decreased substantially, and no styrene oligomers were detected.…”
Section: Resultsmentioning
confidence: 99%
“…Early studies of pyrene degradation by O 3 were carried out in different organic solvents including methanol [4], and t-alcohol [5]. Kefely et al [6] studied the kinetics and mechanism of ozone with polystyrene using CCl 4 as a solvent. Lugube et al [7] identified byproducts from ozonation of a concentrated naphthalene solution using H 2 O/CH 3 OH (50/50, v/v) as the cosolvent and found a reaction stoichiometric ratio of 2 moles of O 3 per mole of naphthalene removed.…”
Section: Introductionmentioning
confidence: 99%